Pengabdian Masyarakat Internasional: Indonesian Local Wisdom Education di PERSAIT dan Darul Hikmah High School Thailand - Khoiri, Ahmad; Aprilia, Rennanti Lunnadiyah; Supriyanto, Supriyanto; Andika, Alek (Carmin: Journal of Community Service, 2024)
The low expansion of the introduction of local education culture in Indonesia so that it is known abroad, so it is necessary to carry out community service internationally which is facilitated through the NU (Nahdlatul Ulama) higher education community in Indonesia. Indonesia-Thailand internship cooperation through PERSAIT (Indonesia-Thailand Alumni Association) which was carried out at Darul Hikmah High School, Pattani Province, Thailand with a total of 25 activity participants. Implementation of service for 2 days through activity orientation, introduction to Indonesian Local Wisdom Education, questions and answers, and reflection on activities. The method of implementing service is through lectures, demonstrations, and direct questions and answers with activity participants. The results obtained increased participants' understanding of the introduction of local wisdom-based education to pay attention to motivation to learn educational culture and be able to understand global diversity. The participants responded very well to the service activities, as evidenced by the 25 participants, more than 80% responded very well and felt interested in the introduction of education based on local Indonesian wisdom. As a follow-up activity, Darul Hikmah High School Thailand participants have the potential to be participants to continue their education at the NU tertiary level in Indonesia through international collaboration.